PERLINDUNGAN HUKUM TERHADAP ANAK SEBAGAI PELAKU PELECEHAN SEKSUAL MENURUT UNDANG – UNDANG NOMOR 35 TAHUN 2014 TENTANG PERLINDUNGAN ANAK (Study Kasus Di Kawasan Wilayah Kemenkumham BALI) - Gusti Ayu Putri; I Nengah Susrama (Jurnal Hukum Mahasiswa, 2021)
Indonesian children in a broad sense are the next generation of the Indonesian nation who have the rights and obligations to participate in building the Indonesian state and nation. Children as part of the younger generation are an important and decisive initial link in efforts to prepare and realize the future of the nation and state. Based on the constitution in Indonesia, children have a very important and strategic role where it has been explicitly stated that the State will guarantee the rights of every child to the survival, growth and development of children as well as protection against discrimination and violence. However, if the child does not get enough attention from his immediate environment, it is easy for him to do actions that deviate from the legal norms that apply in society. Acts limited to juvenile delinquency until finally lead to criminal acts that require serious legal handling, especially the protection of children's rights in the criminal justice process. Nowadays, crimes involving children are very common. One of them is sexual abuse by children. Either the child is the victim of abuse or the perpetrator of sexual abuse. This happens because of the lack of supervision from parents to children in internet use.